Learning culture as a prerequisite for an institution-wide approach to educational development - Brahm, Taiga; Gebhardt, Anja; Jenert, Tobias
Over the last two decades, the discussion about innovating teaching and learning at higher education institutions (HEI) has concentrated on various core concepts: such as an increased focus on learning outcomes as competencies and more student-centered teaching. These concepts form part of what Barr and Tagg (1995) have termed the "shift from teaching to learning". However, very few approaches have been proposed so far in the scholarly literature on how to actually transfer such normative concepts into the practice of teaching and learning at HEI. In order to sustainably develop the practices of teaching and learning at HEI, it is necessary to comprehend the prerequisites for educational development. The construct of "learning culture" can be seen as a possible concept to explicate these prerequisites. The aims of this study are to (a) propose an institution-wide approach to educational development at HEI and to (b) present a comprehensive instrument to diagnose learning culture as a starting point for educational development. The findings of the study include a first version of the Learning Culture Inventory for HEI. The students' version of the instrument encompasses 12 scales for the individual, 12 for the pedagogical interactions and 5 for the organizational dimension. The assumed basic factor structure of the instruments could be confirmed. With the institution-wide approach to educational development and the Learning Culture Inventory, this study can provide the basis for sustainable developmental initiatives to innovate teaching and learning at HEI.
Keywords: higher education; instrument development; strategy; educational development